Kenya integrates Climate-Smart Agriculture into its Intended Nationally Determined Contribution - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
CCAFS scientists at the Center for International Forestry Research (CIFOR), the World Agroforestry Centre (ICRAF), the International Livestock Research institute (ILRI) and the International Center for Tropical Agriculture (CIAT), provided inputs into the development of Kenya’s Climate-Smart Agriculture Framework Program (CSA-FP), aimed at guiding investments into climate resilient and low carbon agriculture. As of July 2015, the CSA-FP was integrated into Kenya’s Intended Nationally Determined Contribution (INDC) submission to the United Nations Framework Convention on Climate Change (UNFCCC). The INDC identifies both mitigation and adaptation components from the CSA-FP, and lists forestry and other land use sectors where capacity building for GHG inventories with CIFOR and ILRI is a priority. CCAFS scientists also developed a prioritization tool ‘targetCSA’, which the Kenyan government has requested to pilot in preparation of the INDC. Kenya’s INDC aims to reduce the country’s Greenhouse Gas (GHG) emissions by 30% by 2030, relative to a business-as-usual scenario of 132 Mt CO2eq. The Framework Program will draw from a pool of an estimated USD 40 billion in mitigation finance, which will be mobilized by 2030.